PENERAPAN MODEL KOOPERATIF TIPE TGT DALAM PENINGKATAN PEMBELAJARAN MATEMATIKASISWA KELAS V SDN 2 KEDUNG MENJANGAN TAHUN AJARAN 2013/2014 - destama, dini (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application TGT Type Cooperative Model In Increasing Matehematic Learning At Fifth Grade  Students Of SDN 2 Kedung Menjangan In Academic Year Of 2013/2014. The purposes of this research: 1) to describe the steps of TGT type cooperative model, 2) to describe the increasing of Mathematic learning in Fifth Grade Students SDN 2 Kedung Menjangan in academic year of 2013/2014. This research was classroom action research (CAR). This research conducted in three cycles, consisting of planning, action, observation, and reflection. Subjects this research are Fifth Grade Students SDN 2 Kedung Menjangan, amounting to 20 students, consisting of 12 males and 8 females. The conclusions this research is the application of the TGT type can be increasing of Mathematic learning at Fifth Grade Students of SDN 2 Kedung Menjangan in academic year of 2013/2014.Keywords: TGT,Mathematic,Learning